The effects of temporo mandibular joint disorder with clicking symptom on children mastication performance in Deutero Malay race children aged 12-15 years - Hartman, Henri; Pertiwi, Arlette Suzy Puspa; Runkat, Jakobus; Herdiyati, Yetty; Oewen, Roosje Rosita (Padjadjaran Journal of Dentistry, 2014)
Temporo Mandibular Joint Disorder (TMD) could be caused by forward head posture. Articular sound/TMJ clicking is the most often sign and symptom for TMD that could happen in human being. The presence of TMD such as TMJ clicking would cause an imbalance masticatory system. The purpose of this research is to investigate TMJ clicking effects to masticatory performance. This research was cross-sectional study with a type of epidemiology survey. Subject were children aged 12-15 years old Deutero-Malay sub-races Live in Bandung and was taken using multi-stage random sampling technique. Subject; consisted of 24 children as control group and 28 children as TMJ clicking group. Both group were then checked for masticatory performance using multiple sieve method and 20x chewing of artificial test food. Mastication performance value represented by median particle size (MPS) particle distribution (b) for each group. MPS from TMJ clicking group (3.0571,SD=0.9990) showed higher value than control group (2.28958,SD=0.66838). Statistic analysis with t-test showed that there’s a significant result in both of group (pvalue=0,0024, α = 0,05). Conclussion, temporo mandibular joint clicking subject has lower masticatory performance.